Uang Panai’ as Cultural Symbolism and Economic Burden in Bugis Marriage Traditions: A Phenomenological Study - Anggraini, Dea Pricilia; Puput T, Astuti Rada; Sakaor, Diva Srani; Paranoan, Natalia; Beloan, Bertha (Journal of Development Research, 2025)
This study aims to describe the Bugis people’s perceptions of Uang Panai’ as an economic burden in the context of traditional marriage, as well as to explain its symbolic meaning from cultural and economic perspectives. The research was conducted in Makassar, a modern metropolitan city, using qualitative methods with an interpretive paradigm and phenomenological analysis approach. Primary data were collected directly from the research subjects through in-depth interviews with 11 informants, consisting of community leaders, religious leaders, parents, and young people. The findings indicate that the perception of Uang Panai’ as an economic burden can be reduced by providing broader understanding to the Bugis community regarding the cultural importance of this tradition. When properly understood, Uang Panai’ is viewed not as a burden but as a symbol of strength, sincerity, and commitment between families. It also encourages individuals to work harder in preparation for marriage so that the tradition can continue to be preserved. The implications of this study highlight the importance of preserving the Uang Panai’ tradition as part of Bugis cultural heritage. The practice should be maintained and passed down to future generations while emphasizing the value of kinship. This ensures that communication between families is well-established and that the determination of Uang Panai’ remains considerate and does not impose undue burdens on either party.